A life cycle exergy-based analysis of Power-to-liquid/Power-to-gas hybrid processes coupled with different water electrolysis technologies - Gao, Ruxing; Wang, Lei; Zhang, Leiyu; Zhang, Chundong; Jun, Ki Won; Kim, Seok Ki; Zhao, Tiansheng; Wan, Hui; Guan, Guofeng (Fuel, 2024)
In the past decades, Power-to-Liquid (PTL) and Power-to-Gas (PTG) technologies, which utilize the captured CO2 and surplus renewable electricity to produce sustainable fuels and chemicals, have attracted much attention. In our previous study, four PTL/PTG process cases coupled with different water electrolysis technologies (i.e., AWE, PEM, SOEC, and AEM) have been proposed to simultaneously produce syncrude and SNG. To comprehensively examine their technical, economic, and environmental performances, this paper carried out an exergy-based (i.e., exergoeconomic and exergoenvironmental) analysis. Firstly, a Life Cycle Assessment (LCA) was plotted with the material and energy flows data to evaluate the tangible and potential environmental impacts. Secondly, an exergoeconomic and exergoenvironmental analysis that integrate exergy analysis with economic analysis and LCA was suggested to calculate the integrated technical–economic and technical-environmental performances. The formation of exergoeconomic cost and exergoenvironmental impacts in the four cases are illustrated by Sankey diagrams. The results revealed that the case coupled with AEM electrolysis technology has the lowest exergoeconomic product cost and exergovironmental potential emissions. In the certain cases, the components with considerable energy consumption and temperature changes are the main contributors for the total exergoeconomic cost and exergoenvironmental impacts. Regarding the results, this work intends to provide optimization suggestions, aiming at achieving a balance among the better technical and economic performances and less environmental impacts.
Keywords: Exergoeconomic analysis; Exergoeconomics; Exergoenvironmental analyse; Liquid power; Power; Power-to-gas; Power-to-liquid; Technical performance; Water electrolysis; Exergoeconomic analysis; Exergoenvironmental analysis; Power-to-gas; Power-to-liquid; Water electrolysis